TAHAP PERKEMBANGAN WISATA KAMPUNG GERABAH BLITAR BERDASARKAN TEORI TOURISM AREA LIFE CYCLE - Lutfiana, Maya; Purnomo, Agus (UHN IGB Sugriwa Denpasar, 2025)
Kampung Gerabah Tourism is the only pottery educational tour in the Blitar area. The tour has been established since 2014. Ideally, with 11 years of age, this tour should have been established and able to attract a significant number of tourist visits. However, findings in the field indicate that the growth in the number of tourist visits is still relatively low. This study aims to identify the development stage of Kampung Gerabah Blitar Tourism by examining tourism elements including attractions, accessibility, amenity, accommodation, and tourist visits which are then analysed using the Tourism Area Life Cycle theory. The method used is a qualitative approach with a case study design. The data in this study includes the number of tourist visits, tourism managers, attractions, accessibility, accommodation, amenity, and the process of tourism activities. The data were obtained from purposive respondents through observation, interviews, and documentation. Data analysis was carried out through data collection, data reduction, data presentation, and conclusion drawing. The results showed that attractions are interesting, while accessibility needs improvement with information boards and directions. The amenity is enough to support the needs of tourists. Meanwhile, lodging accommodation is in the process of being built. Overall, the development of Kampung Gerabah tourism is in the pre-involvment stage, which can be seen from the appearance of the initial signs towards the involvment stage. The implication of this research is to identify the development stage of Kampung Gerabah Tourism so that it can be used by managers in formulating tourism development strategies.